O cuidador como mediador no ensino de habilidade de engajamento conjunto para crianças com autismo - SANTOS, Adrine Carvalho dos (Universidade Federal do Pará, 2019)
Children with autism are characterized by significant deficits to engage in behaviors coordinated attention (CA). The CA impairment interfere with development of the child's attentional states, involving the joint engagement with each other. Hence, the use of interventions based on teaching this skill is becoming increasingly common. Results from various studies indicate that skills training targeted at parents is associated with increased communication and social skills of children with autism. The present study aimed to investigate the effectiveness of the intervention with caregivers program, based on the proposed by Kasari et al (2010) and examine the relationship between the caregiver responsiveness and engagement whole attention, and maintenance of new repertoire three months after completion the study (follow-up). Participants were seven caregivers and their children diagnosed with autism, aged between 47 and 67 months. The intervention program administered with the caregivers lasted two months, and consisted of four group meetings four individualized monitoring. Filming of moments of interaction between child and caregiver were performed in all phases of the study for further analysis, in addition, other measures were administered, they are, Social Interaction Scale, ABFW Test (pragmatic language) and Scale of Adherence to Training . The results indicated significant differences in the duration of the joint engagement (p = 0.016) and non-joint (p = 0.018) measured before and after the intervention, the Wilcoxon test for repeated measures showed significant differences (p = 0.016) in the behavior of caregivers after the intervention, there were no significant changes in pragmatic language of children. The data indicated that the course promoted changes in the pattern of engagement of the child with the caregiver and also promoted an increase in the responsiveness of caregivers, and these gains were maintained during the session seguimento.Os findings were relevant to strengthen the importance of develop intervention programs that empower parents to promote improvements in sociocomunicativas skills of their children with autism.